2022
DOI: 10.1111/bjh.18467
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic haematopoietic cell transplant in patients with relapsed/refractory anaplastic large cell lymphoma

Abstract: Summary The prognosis of relapsed/refractory (R/R) anaplastic large cell lymphoma (ALCL) is poor. Large studies evaluating outcomes of allogeneic haematopoietic cell transplantation (allo‐HCT) in systemic R/R ALCL are not available. Using the Center for International Blood and Marrow Transplant Research (CIBMTR) database, we evaluated outcomes of 182 adults (aged ≥18 years) with R/R ALCL undergoing allo‐HCT between 2008 and 2019. Non‐relapse mortality (NRM), disease relapse/progression (REL), progression‐free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…A large cohort study performed by the Center for International Blood and Marrow Transplant Research (CIBMTR) found that patients with relapsed ALCL undergoing auto-HCT had superior outcomes to those receiving allo-HCT with a smaller nonrelapse mortality at 100 days, 1 year, and 3 years, and superior PFS and OS at 1 and 3 years for the auto-HCT patients compared to allo-HCT patients, although this study also did not separate ALCL based on ALK status and patients had varying baseline characteristics 36 . An analysis of the CIBMTR database of 182 ALCL patients receiving allo-HCT that similarly did not separate patients based on ALK status did find that allo-HCT for relapsed/refractory ALCL had a 5-year pFS of 41% and OS of 56%, indicating that allo-HCT can play an effective role in treating relapsed/refractory disease 37 . A recent meta-analysis comparing auto-HCT to allo-HCT in relapsed/refractory PTCL patients showed benefits to both types of HCT depending on the patient population, finding some benefit to allo-HCT in patients with a higher-risk disease stage agent 38 .…”
Section: Salvage Therapymentioning
confidence: 99%
“…A large cohort study performed by the Center for International Blood and Marrow Transplant Research (CIBMTR) found that patients with relapsed ALCL undergoing auto-HCT had superior outcomes to those receiving allo-HCT with a smaller nonrelapse mortality at 100 days, 1 year, and 3 years, and superior PFS and OS at 1 and 3 years for the auto-HCT patients compared to allo-HCT patients, although this study also did not separate ALCL based on ALK status and patients had varying baseline characteristics 36 . An analysis of the CIBMTR database of 182 ALCL patients receiving allo-HCT that similarly did not separate patients based on ALK status did find that allo-HCT for relapsed/refractory ALCL had a 5-year pFS of 41% and OS of 56%, indicating that allo-HCT can play an effective role in treating relapsed/refractory disease 37 . A recent meta-analysis comparing auto-HCT to allo-HCT in relapsed/refractory PTCL patients showed benefits to both types of HCT depending on the patient population, finding some benefit to allo-HCT in patients with a higher-risk disease stage agent 38 .…”
Section: Salvage Therapymentioning
confidence: 99%